2014
DOI: 10.1021/ar5002582
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry in Motion: Tiny Synthetic Motors

Abstract: Diffusion is the principal transport mechanism that controls the motion of solute molecules and other species in solution; however, the random walk process that underlies diffusion is slow and often nonspecific. Although diffusion is an essential mechanism for transport in the biological realm, biological systems have devised more efficient transport mechanisms using molecular motors. Most biological motors utilize some form of chemical energy derived from their surroundings to induce conformational changes in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
86
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(89 citation statements)
references
References 53 publications
1
86
0
1
Order By: Relevance
“…References [38,40] show that this result is the zeroth order term of the solution for surface films of non-vanishing thickness. This means that corrections in δ/R become important as the radius of the colloid decreases [84]. Reference [37] has shown that accounting for chemical kinetics which are not completely reaction-limited, i.e., Da = 0, also leads to a dependence of the phoretic velocity on the particle size; this theoretically predicted dependence agrees well with the experimental observations.…”
Section: Discussionsupporting
confidence: 59%
“…References [38,40] show that this result is the zeroth order term of the solution for surface films of non-vanishing thickness. This means that corrections in δ/R become important as the radius of the colloid decreases [84]. Reference [37] has shown that accounting for chemical kinetics which are not completely reaction-limited, i.e., Da = 0, also leads to a dependence of the phoretic velocity on the particle size; this theoretically predicted dependence agrees well with the experimental observations.…”
Section: Discussionsupporting
confidence: 59%
“…One might therefore also assume that "nanoswimmers" are described by continuum hydrodynamics, although this is an assumption, as there is currently no complete theoretical description of (the hydrodynamics) of a catalytically active nanoparticle. A theoretical treatment that considers the scaling behaviour of diffusiophoretic particles has recently appeared [5]. These authors conclude on the basis of particle-based simulations of chemically powered Janus ∼ nm motors that the principle of self-diffusiophoresis still operates at the nanoscale, even though the motion is subject to strong fluctuations [5].…”
Section: Insights From Theorymentioning
confidence: 99%
“…A theoretical treatment that considers the scaling behaviour of diffusiophoretic particles has recently appeared [5]. These authors conclude on the basis of particle-based simulations of chemically powered Janus ∼ nm motors that the principle of self-diffusiophoresis still operates at the nanoscale, even though the motion is subject to strong fluctuations [5].…”
Section: Insights From Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Self-propulsion is achieved by the generation of local gradients of chemical concentrations, electrochemical potential, or temperature, which produce the force driving the motor [6][7][8][9][10][11]. This is the case in particular for Janus motors with catalytic and chemically-inactive hemispheres, moving by diffusiophoresis in a solution with out-of-equilibrium concentrations of fuel and product [11][12][13][14]. The propulsion mechanism is based on the mechanochemical coupling between the fluid velocity around the motor and the concentration fields induced by the reaction taking place on the catalytic hemisphere.…”
mentioning
confidence: 99%